Produktifitas Hijauan Pakan Ternak Di UPT. Agroscience Teknopark Fakultas Peternakan Universitas Islam Lamongan - Fitria Dwi Cahyani; M. Muhid Mustofa Afifudin; Rosyad Haqiqi Hamadullah; Alfian Adi Atma (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2022)
Abstract Grazing with a free range system uses a forage cropping pattern aimed at providing feed throughout the year. This study aims to study forage quality and pasture productivity managed by UPT. Agroscience Teknopark Faculty of Animal Husbandry Lamongan Islamic University by taking forage samples from 3 pastures. Forage samples in fresh form were collected at 3 different sampling points in each paddock by using a metered quadrant plate measuring 0.5x0.5 m. Fresh samples were weighed and then sorted by plant species for identification of the botanical composition. The sample is then mixed again, to be dried. Parameters measured include forage mass production, botanical composition, and capacity. The results showed that there are 7 types of species that grow in the pasture, namely 5 gramineae, 1 leguminosae and 1 type of weed. The average mass production of forage in fresh form is around 22.70 t/year, and forage in dry form is around 20.25 t/year, with a capacity of 6.52 AU Keyword : Fresh Forage Production, Dry Forage Production and Holding Capacity.